Healthy Dietary Intake Behavior Potentially Modifies the Negative Effect of COVID-19 Lockdown on Depression: A Hospital and Health Center Survey - Pham, Khue M.; Pham, Linh V.; Phan, Dung T.; Tran, Tien V.; Nguyen, Hoang C.; Nguyen, Minh H.; Nguyen, Huu C.; Ha, Tung H.; Dao, Hung K.; Nguyen, Phuoc B.; Trinh, Manh V.; Do, Thinh V.; et al. (Frontiers in Nutrition, 2020)
Background: The COVID-19 pandemic causes a huge burden for affected countries. Several public health interventions were applied to contain the infection. However, the pandemic itself and the lockdown measure negatively influence people’s lifestyles, psychological health. Purpose: To explore determinants of healthy dietary intake, depression, and examine the interaction between healthy dietary intake and COVID-19 lockdown on depression. Methods: A cross-sectional study was conducted at 18 hospitals and health centers 14 February-31 May 2020. Data of 8291 outpatients were collected including patients’ characteristics, clinical parameters, health literacy, healthy dietary intake (using the healthy eating score, HES), other health-related behaviors, and depression (using the patient health questionnaire, PHQ). Depression was defined as PHQ score ≥ 10. Results: Protective factors of healthy dietary intake and depression were higher education, better medication payment ability, higher social status, more physical activity, and higher health literacy. Whereas older age, ever married, own business or other types of occupation, lockdown, suspected-COVID-19-symptoms, and comorbidity were associated with lower HES scores and a higher depression likelihood. Besides, overweight/obesity, and alcohol drinking were associated with lower HES scores. As compared to patients not under lockdown and with lowest HES score, those who under lockdown and with lowest HES score had 10.6 times higher depression likelihood (odds ratio, OR, 10.60; 95% confidence interval, 95%CI, 6.88, 16.32; p < 0.001), while people with higher HES score had 15% lower depression likelihood (OR, 0.85; 95%CI, 0.82, 0.89; p < 0.001). Conclusions: Healthy dietary intake and depression were determined by several socio-demographic, clinical, and behavioral factors. Lockdown measure affects people’s dietary intake behavior and depression. Importantly, healthy dietary intake potentially modifies the negative effect of lockdown on depression.